Nematode Interactions on Beetle Hosts Indicate a Role of Mouth-Form Plasticity in Resource Competition - Renahan, Tess; Sommer, Ralf J. (Frontiers in Ecology and Evolution, 2021)
Competition is rampant across kingdoms, arising over potential mates, food resources, or space availability. When faced with opponents, phenotypic plasticity proffers organisms indispensable advantageous strategies to outcompete rivals. This tactic is especially crucial on decaying insect hosts as myriad microbes and numerous nematodes struggle to establish thriving populations and ensure resource availability for future generations. Scarab beetles and their associated nematode symbionts on La Réunion Island have provided exceptional systems to study complicated cross-phylum interactions in soil, and recently we have identified a previously unexplored beetle host, Gymnogaster bupthalma, to be reliably co-infested with diplogastrids Pristionchus mayeri and Acrostichus spp. These nematodes maintain the capacity to plastically respond to environmental conditions by developing disparate mouth forms, a strict bacterial-feeding morph or an omnivorous morph that enables predation on other nematodes. In addition, under stressful settings these worms can enter an arrested development stage called dauer, non-feeding dispersal larvae that resume development into reproducing adults when conditions improve. By investigating this beetle-nematode system in a natural context, we uncovered a novel Pristionchus strategy, wherein dauer dispersal from the carcass is gradual and a reproducing population is sustained. Remarkably, usually preferential-bacterial morph P. mayeri develop as predators in populations dense with competitors.